Water Requirements and Water Use Efficiency of Aceh Patchouli (Pogostemon cablin Benth.) at Low Light Intensity - Taufan Hidayat; Filly Dwifandi; Hasanuddin Hasanuddin; Trisda Kurniawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Aceh Patchouli is a C3 plant that does not require high water input and full light intensity to grow optimally, making it suitable for intercropping under main crops. This study aimed to determine the water requirements and adaptability of two Aceh patchouli varieties (Tapak Tuan and Sidikalang) under low light conditions using artificial shade. The experiment employed a nested box design with two factors: shade levels and plant varieties. Observed variables include macroclimate, microclimate, and agronomic parameters such as plant height, number of leaves, leaf area, dry leaf weight, and total biomass. Water requirement and water use efficiency (WUE) were also analyzed. Results showed that shading reduced plant water needs: 33.29% L/plant without shade, 32.80 L/plant under 30% shade (1.5% reduction), and 30.30 L/plant under 60% shade (9% reduction). The Tapak Tuan variety had a higher water requirement (33.30 L/plant) compared to Sidikalang (30.96 L/plant). Importantly, increasing shade levels led to improved water use efficiency, although the variety did not significantly influence WUE.  The findings indicate that the use of shade in patchouli cultivation not only conserves water but also enhances efficiency, supporting its potential for sustainable intercropping systems in shaded or water-limited environments.